Processing design: reflexões sobre design gerativo - Valério, José Henrique (2013)
The Processing language programming can be considered a pluralistic language. It is used in works ranging from design to their association with the use of the logic board Arduino, with which it is possible to control systems with applications in the field of 3D printing, robotics, transportation engineering, and others. All of them this vastness applications, this research focuses on Processing language programming while design. It seeks to understand, from a historical and conceptual as well as the analysis of the works of some contemporary artists from Brazil and abroad, the existence of the unpredictability of this type of design, purposing to study the processing design and their applications. The generative structure will be faced with the cultural design tradition propagated today in schools and by designers. Therefore, this project It starts with the practical-theoretical reflection: presents a series of examples of processing design developed by professionals based on questions and clarifications raised throughout the research process, contributing to the understanding and suggesting new avenues for research on processing design and new technologies.